Innovative Analysis of the Sequenced Patterns of Vancomycin-Resistant Enterococci Strains to Determine Clonal Transmission in a Hospital Setting. (2nd September 2015) - Chemaly, Roy F.; Ghantoji, Shashank S.; Huber, Thomas; Raad, Issam I.; Jinadatha, Chetan; Stibich, Mark
Abstract : Isolates from patients who acquired vancomycin-resistant enterococci (VRE) were examined for the frequency of genetically indistinguishable strains on leukemia and stem cell transplant units at a major cancer center for 1 year. A total of 14 strains recurred, primarily on the same floor and in the same service unit an average of 49 days apart. Infect. Control Hosp. Epidemiol. 2015;36(12):1461–1463